A century of “Camel Research”: a bibliometric analysis - Kandeel, Mahmoud; Morsy, Mohamed A.; Abd El-Lateef, Hany M.; Marzok, Mohamed; El-Beltagi, Hossam S.; Al Khodair, Khalid M.; Soliman, Wafaa E.; Albokhadaim, Ibrahim; Venugopala, Katharigatta N. (Frontiers in Veterinary Science, 2023)
Bibliometrics is a quantitative analytic strategy used to assess the unit of publications per each field of research. Bibliometric studies are commonly employed to examine the current research climate, potential developments, and development trends in certain domains. In this work, the major contributors to camel research throughout the past century are discussed, along with the funding sources, academic institutions, scientific disciplines, and countries that contributed to “Camel Research”. There are 7,593 articles dedicated to camel research on the Web of Science (as of August 1st, 2022). Three stages were involved in the publication of a study on camels. At the beginning, from 1877 to 1965, there were fewer than ten new publications per year. The second stage comprised 100 publications per year (1968-2005). Since 2010, nearly 200 new papers have been published each year. King Saud and King Faisal universities contributed > (0.08) of the total publications. While more than 1,000 funding agents were retrieved, the Natural Science Foundation of China (NSFC) showed the greatest rate of funded projects (0.17). Camel research was included in 238 scientific disciplines. The top disciplines were Veterinary Sciences (0.39), Agriculture Dairy Animal Science (0.144), and Food Science Technology (0.087). Overall, there has been an increase in interest in camels in recent years, but the research trends in camel health and production need greater support.